The InSe/SiH type-II van der Waals heterostructure as a promising water splitting photocatalyst: a first-principles study. Issue 37 (18th September 2020) - Sheng, Wei; Xu, Ying; Liu, Mingwei; Nie, Guozheng; Wang, Junnian; Gong, Shijing
Abstract : The type-II band alignment promotes InSe/SiH as a high efficiency photocatalyst for water splitting in visible light. Abstract : Photocatalytic water splitting for hydrogen production has attracted increasing research attention in recent years, and great efforts have been made in order to find the ideal photocatalyst. In this work, we proposed a two-dimensional material-based van der Waals (vdW) heterostructure constructed by vertically stacked indium selenide (InSe) and silicane (SiH) and studied the feasibility of using it as a possible photocatalyst for water splitting by using first-principles methods. The results show that the InSe/SiH is a direct band gap semiconductor with appropriate gap value and band edge position for photocatalysts in water splitting. Importantly, this heterostructure presents type-II band alignment at the equilibrium configuration, which supports the effective separation of photoexcited electrons and holes. A built-in electric field set up within the interface of the heterostructure will further hinder the electron–hole recombination and thus improve the photocatalytic efficiency. In addition, compared with separated InSe and SiH monolayers, the heterostructure exhibits enhanced light absorption capabilities in ultraviolet and visible light regions. These findings indicate that the InSe/SiH vdW heterostructure is a promising candidate for photocatalysts for solar water splitting.